GE_GERICHTE P/5933/2019 vom 4. Juli 2024 - GE Cour de justice (2024)
RECOURS JOINT;DÉCISION D'IRRECEVABILITÉ;CONTRAINTE SEXUELLE;VIOL;PRESSION;TRAITEMENT AMBULATOIRE;FIXATION DE LA PEINE | CP.189; CP.190; CP.187; CP.63